Medical Staff at Sanatorium-Resort Organizations: Working Conditions and Health Risk Factors - Nikolay A. Meshkov; Anatoliy D. Fesyun; Maxim Yu. Yakovlev; Andrey P. Rachin; Elena A. Valtseva (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
Medical staff working conditions are characterized by a range of adverse workplace factors investigated primarily at hospital organizations. However, sanitary audit of working conditions and health risk factors for medical workers in the sanatorium-resort industry is also a task that needs attention. Aim. To analyze the results of the working conditions special assessment and identify the main work-related factors affecting health state of medical staff at sanatorium-resort organizations. Material and methods. Scientific search and analysis of publications on the safety of working conditions and health protection of medical workers. Systematization of research materials, statistical and comparative analysis of the results of working conditions special assessment carried out at branches of the Medical Research Center and data provided in publications. Results. Medical staff are exposed to a wide range of hazards. Work-related factors that do not meet established hygiene standards cause the greatest concern among medical workers. These are microclimate, lighting and working equipment (47.0%, 37.8% and 24.0%, respectively). A number of devices inspected in the physiotherapy room exceeded hygienic standards for alternating electric and magnetic field intensity. Analysis of air pollution in the physiotherapy department working area showed that some of the harmful chemicals exceeded permissible exposure limits. The results of the special assessment of working conditions performed at branches of the Medical Research Center showed that a high percentage of medical workers was exposed to harmful biological factors and high severity of the labor process. Conclusion. Physical and chemical factors are the greatest workplace hazards for healthcare workers at health resorts. However, a special assessment of working conditions showed that the biological factor was the most significant one across all professional groups.